NOGAIS UPRISING IN 1916 - Kidirniazov, D S (History, Archeology and Ethnography of the Caucasus, 2015)
The article shows how during the First World War the Russian authorities demanded to recruit volunteers to participate in the war. Forced mobilization and violent protests from the local population turned into an armed rebellion: uprising of the Nogais in 1916 was ruthlessly stamped out by the royal troops. It should be noted that the anti-war actions of the Nogais of the North-East Caucasus in 1916 occupy a prominent place in the history of the public liberation struggle of the peoples of the national outskirts of Russia during the First World War.